Protective Effects of Flavanol-Rich Dark Chocolate on Endothelial Function and Wave Reflection During Acute Hyperglycemia - Grassi, Davide; Desideri, Giovambattista; Necozione, Stefano; Ruggieri, Fabrizio; Blumberg, Jeffrey B.; Stornello, Michele; Ferri, Claudio (Hypertension (Dallas, Tex. 1979), 2012)
Nitric oxide plays a pivotal role in regulating vascular tone. Different studies show endothelial function is impaired during hyperglycemia. Dark chocolate increases flow-mediated dilation in healthy and hypertensive subjects with and without glucose intolerance; however, the effect of pretreatment with dark chocolate on endothelial function and other vascular responses to hyperglycemia has not been examined. Therefore, we aimed to investigate the effects of flavanol-rich dark chocolate administration on (1) flow-mediated dilation and wave reflections; (2) blood pressure, endothelin-1 and oxidative stress, before and after oral glucose tolerance test (OGTT). Twelve healthy volunteers (5 males, 28.2±2.7 years) randomly received either 100 g/d dark chocolate or flavanol-free white chocolate for 3 days. After 7 days washout period, volunteers were switched to the other treatment. Flow-mediated dilation, stiffness index, reflection index, peak-to–peak time, blood pressure, endothelin-1 and 8-iso-PGF2α were evaluated after each treatment phase and OGTT. Compared with white chocolate, dark chocolate ingestion improved flow-mediated dilation (P=0.03), wave reflections, endothelin-1 and 8-iso-PGF2α (P<0.05). After white chocolate ingestion, flow-mediated dilation was reduced after OGTT from 7.88±0.68 to 6.07±0.76 (P=0.027), 6.74±0.51 (P=0.046) at 1 and 2 h after the glucose load, respectively. Similarly, after white chocolate but not after dark chocolate, wave reflections, blood pressure, and endothelin-1 and 8-iso-PGF2α increased after OGTT. OGTT causes acute, transient impairment of endothelial function and oxidative stress, which is attenuated by flavanol-rich dark chocolate. These results suggest cocoa flavanols may contribute to vascular health by reducing the postprandial impairment of arterial function associated with the pathogenesis of atherosclerosis.